Corduroy mansions - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Corduroy Mansions novel, 2010)
Alexander McCall Smith captures the goings on of the residents and visitors at Corduroy Mansions, Pimlico, from nasty Liberal Democrat MP Oedipus Snark to the newest resident, Pimlico Terrier Freddie de la Hay.